Interleukin 1, Interleukin 6, Interleukin 10, and Tumor Necrosis Factor α in Active and Quiescent Systemic Lupus Erythematosus. (June 2014) - Cigni, Alessandro; Pileri, Piera Veronica; Faedda, Rossana; Gallo, Paola; Sini, Annalisa; Satta, Andrea Ercole; Marras, Riccardo; Carta, Elisabetta; Argiolas, Davide; Rum, Iolanda; Masala, Antonio
Objectives: Several studies have investigated the cytokine profile of patients with systemic lupus erythematosus (SLE); however, their role is still controversial, mostly because SLE has a heterogeneous disease manifestation. We measured 4 of the most important cytokines in patients with SLE after dividing them in uniform groups according to disease activity and organ involvement. Materials and Methods: Eighty-two adult female patients with SLE were divided into 3 groups according to disease activity and organ involvement: Group A (SLE activity index [SLEDAI] score, 7 ± 0.4) included subjects with newly diagnosed, active SLE, investigated before starting therapy. Group B (SLEDAI score, < 6) included patients without renal involvement, treated with prednisone and azathioprine or hydroxychloroquine. Group C (SLEDAI score, < 6) included patients with lupus nephritis, treated with methylprednisolone and cyclophosphamide, reaching complete remission. Fourteen healthy females served as controls. Results: Interleukin-1 levels were 1.0, 0.8, 0.7, and 0.25 pg/mL in groups A, B, C, and D, respectively. Interleukin-6 levels were 3.2, 3.6, 4.0, and 1.4 pg/mL in groups A, B, C, and D, respectively; Il-10 levels, 3.05, 1.1, 1.5, and 1.65; tumor necrosis factor-α levels, 8.75, 5.8, 5.4, and 3.6. Interleukin 1, IL-6, and tumor necrosis factor-α were significantly higher in the patients with SLE than in the healthy controls; IL-1 was significantly higher in group A than in group C. Interleukin 10 showed positive correlation with C-reactive protein, whereas it showed negative correlation with C3. Conclusions: Data from our cohort, one of the largest so far reported, add to the evidence that proinflammatory cytokines such as Interleukin-1, Interleukin-6, Interleukin-10 and tumor necrosis factor-α are important in SLE pathogenesis.